STRUKTUR BERTINGKAT DAN RANGKA BETON GAYA EROPA PADA BANGUNAN RAADHUIS (WATERTOREN) KOTA PALEMBANG: STRUKTUR BERTINGKAT DAN RANGKA BETON GAYA EROPA PADA BANGUNAN RAADHUIS (WATERTOREN) KOTA PALEMBANG - Irwanto, Dedi; Andhifani, Wahyu Rizky; Apriani, Evy; Wahyudi, Wanny Rahardjo (Berkala Arkeologi, 2024)
This article discusses the use and function of raadhuis buildings, as well as water towers in Palembang City. This building has a multi-story structure with a concrete frame. The mayor of d'Armandville initiated the design of this building, a concept that Lissa Nessel, the subsequent mayor, carried forward. In this article, we will discuss buildings and non-buildings in the form of reinforced concrete from the construction of raadhuis and water tower buildings during that period, including notes on the development of the Palembang city hall complex, which has not been widely disclosed. Using archaeological and historical data, the aim of writing this article is to examine the development of the use, function, and expert design of this building complex, both during the colonial period and today. We conducted the research in four stages of archaeological-historical study: data collection, data analysis, data processing, and data writing. We cannot separate the results of the study of multi-story structures with concrete frames from the presence of the elite contractor Hollandsche Beton Maatschapij NV (HBM), based in Talang Jawa, Palembang. HBM was an early investor in the city of Palembang, which developed reinforced concrete as a structural material that was able to properly distribute construction loads evenly. So, architect S. Snuyf's design of Palembang City Hall can accommodate various structural elements. The presence of reinforced concrete from the Raadhuis construction triggered the construction of other reinforced concrete buildings in the city of Palembang.